Histological analysis of vertebral disc herniations in patients with different age groups - Radchenko, Volodymyr; Piontkovsky, Valentyn; Dedukh, Ninel (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Studying of degenerative changes in the structure of vertebral discs and peculiarities of microscopic organization in patients with different age groups gives us possibility to connect pathomorphological changes with clinical symptoms. Objective: to study the peculiarities of herniations structure which were obtained after surgeries in patients of different age groups. Methods: herniations of vertebral discs on the levels LIII–LIV, LIV–LV и LV–SI were obtained after surgeries of 4 3 patients (24 women, 19 men) of three age groups: the 1st — 25–44 y. o, the 2nd — 45– 60, the 3rd — 61–75. We used histology with semiquantitative estimation (score) of degenerative changes. Results: it was shown that the sex has not influence on the severity of degenerative changes of herniations. According to some histological signs we concluded distinctive features. It was found that in the 1st group in the samples there were mostly chondrons which contained more than 15 chondrocytes with large cores, it testifies of proliferation and hypertrophy. Severe destructive lesions of matrix were not found. With aging degenerative changes in herniations are progressed. So the number of large chordons was in 1.7 and 1.4 times lower in the 2nd group compare to the 1st one. Fibroblasts accumulation increased in the matrix (in 3 and 3.2 times in men and women), small foci of granular destruction and chondrogenesis appeared, areas with increased dense of fibroblasts, small bone sequestrations (21.4 %). In the 3rd group in men and women the number of chondrons in herniations were decreased in 2.6 and 2.3 times compare to the 1st group. Areas of defibration in the matrix became wider in 2.4 and 2 times, granular destruction — in 1.3 and 1.4 times. Large areas were with chondrogenesis and in 78.6 % of cases we have found small bone fragments. Conclusion: with aging the severity of destructive changes in herniations increase significantly.